Can different polymerization times affect the surface microhardness, water sorption, and water solubility of flowable composite resins? (Bioscience Journal, 2023)
This in vitro study evaluated and compared the effects of different polymerization times on the surface microhardness, water sorption, and water solubility of flowable composite resins. Three flowable composite resins [Es Flow (ESF), IGOS Flow (IGF), Estelite Flow Quick (EFQ)] were tested in this study. Each flowable composite resin (n = 7) was polymerized in a disc-shaped mould (1x10 mm) with an LED light-curing unit (D Light Pro) for two different times (20 and 40 sec.). The top surfaces of all specimens were polished (Sof-Lex). The surface microhardnesses of the flowable composite resins were measured with a Vickers HMV microhardness tester. Water sorption and water solubility were calculated according to the ISO 4049 standard. One-way ANOVA and post hoc Tamhane, Dunnett, and Tukey tests were used in the statistical analyses. Pearson’s and Spearman’s rho correlation tests were used to assess possible correlations between the different variables. The results were evaluated with a significance of p